Towards the high-accuracy determination of the 238U fission cross section at the threshold region at CERN – n_TOF - Diakaki M.; Audouin L.; Berthoumieux E.; Calviani M.; Colonna N.; Dupont E.; Duran I.; Gunsing F.; Leal-Cidoncha E.; Le Naour C.; Leong L.S.; Mastromarco M.; et al. (EPJ Web of Conferences, 2016)
The 238U fission cross section is an international standard beyond 2 MeV where the fission plateau starts. However, due to its importance in fission reactors, this cross-section should be very accurately known also in the threshold region below 2 MeV. The 238U fission cross section has been measured relative to the 235U fission cross section at CERN – n_TOF with different detection systems. These datasets have been collected and suitably combined to increase the counting statistics in the threshold region from about 300 keV up to 3 MeV. The results are compared with other experimental data, evaluated libraries, and the IAEA standards.